Effect of an Ultrasound Pre-Treatment on the Characteristics and Quality of Far-Infrared Vacuum Drying with Cistanche Slices - Chunhui Jiang; Fangxin Wan; Zepeng Zang; Qian Zhang; Guojun Ma; Xiaopeng Huang (Foods, 2022)
In this study, the effect of an ultrasound (US) pre-treatment on the process of drying Cistanche slices through far-infrared vacuum drying was investigated with various experimental factors, including the US treatment time (25, 35, 45 min), frequency (20, 40, 60 kHz) and power (150, 180, 210 W). The results showed that compared with the samples without US, the material drying time after the US treatment was reduced by 16–36.8%. The effective moisture diffusion coefficients of Cistanche slices under different US conditions ranged from 1.61122 × 10−8 to 2.39274 × 10−8 m2/s, which agreed with food processing ranges. In addition, the phenylethanoid glycoside, iridoid, polysaccharide, total phenol and total flavonoid contents in Cistanche were significantly increased after US pre-treatment. However, the dried products obtained with the 45 min US treatment had greatly damaged internal structures, collapsed and seriously deformed surfaces, and low contents of active ingredients. Overall, the US pre-treatment could significantly improve the drying quality of Cistanche slices.